Microwave absorption analysis on recycled glass doped with Ferum (II, III) Oxide (Fe2O3) - Che Mansor, M.F. (International Journals of Engineering and Sciences Publisher, 2015)
Composite consisting of recycled glass and Ferum (II, III) Oxide were prepared through a heating process in 1100 Â°C for 4 hours. The prepared composite of recycled glass which is presented in cullet powder and Ferum (II, III) Oxide is an innovation in improving the absorption of microwave signal. Cullet has been found to possess a significant propensity for absorption microwave. In this research, the microwave absorbability of various ratios of cullet powder to Ferum (II, III) Oxide in the composite was investigated. Reflection coefficient (Î) and transmission coefficient (T) are used to determine the absorbability of microwave in range of absorption coefficient of 1.2 GHz to 3.0 GHz. The results show that cullet powder containing Ferum (II, III) Oxide absorbed microwave efficiently from 2.5 GHz to 3.0 GHz. The comparison among the composite in different ratio of Ferum (II, III) Oxide is conducted to determine the best optimum of ratio in microwave absorption. Â© October 2015 IJENS.